Reducing Uncertainties in Hydrocarbon Prediction and Reservoir Delineation using Innovative Geophysical Analysis - SHAMSUDDIN, SYAZA ZUHAIRA (2019)
The application of lithology and fluid indicators has helped the geophysicists to discriminate reservoirs to non-reservoirs from a field.